Tourism Destination Image of Russia in the Perspective of the Portuguese Market - Arslanova, Liliya; Agapito, Dora; Pinto, Patrícia (Journal of Tourism, Sustainability and Well-being, 2017)
In recent decades the importance of destination image has been increasingly analyzed and it is generally considered to be vital in the marketing of destinations. It can be noted that the tourism industry in Russia has not been the subject of a great deal of research with regard to its destination image. Therefore the purpose of this work is to assess Russia’s destination image in the perspective of Portuguese people. The research instrument was an online questionnaire, comprised of open-ended and closed questions. A combination of two software programs, NVivo and IBM SPSS Statistics 21, was employed to analyze the data. This exploratory study suggests that Portuguese peoples’ perceptions of Russia are mostly favorable and they have a high awareness about Russia’s destination features.